KECURANGAN LAPORAN KEUANGAN DI SEKTOR ENERGI INDONESIA: APAKAH PENGUNGKAPAN TATA KELOLA PERUSAHAAN MEMILIKI PERAN? - Isnaylah Cahyani; Ambar Kusumaningsih (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study examines the influence of governance disclosure on financial statement fraud among energy sector companies listed on the IDX during the 2022-2024 period. A quantitative research approach was employed using purposive sampling. The sample consisted of energy sector firms listed on the IDX that published complete financial statement throughout the observation period and had governance disclosure scores available in the Bloomberg Terminal database. Research data were collected from companies’ financial reports and governance disclosure scores and subsequently analyzed using logistic regression with SPSS version 27. The findings reveal that governance disclosure does not significantly affect financial statement fraud. The logistic regression results further indicate that governance disclosure is not statistically significant in explaining the occurrence of fraudulent financial reporting. These results suggest that the existing level of governance disclosure has not been sufficiently effective in mitigating financial statement fraud. Future studies are encouraged to incorporate additional variables that may better explain fraudulent financial reporting practices. Furthermore, to prevent financial statement fraud and make governance disclosure more than compliance mechanism, companies must improve the effectiveness of their governance implementation.